(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
ندرس في هذا البحث متراجحة من نوع نيكولسكي التكاملية لكثيرات الحدود ومتراجحة أخرى تخص الدالة وذلك من أجل حالات مختلفة لـ في الفضاء الموّزن نستخدم وزن لاجير المعمم في الحالتين و على كامل المحور الحقيقي باستثناء الصفر. In this research, we study integral Nikolskii inequality for polynomials and another inequality for the function for different casesof ,in the weighted space usinggeneralized Laguerre weights ,for both the cases of this space and ,on all real axis without 0.